Cover Picture: Potential‐Dependent Adlayer Structure and Dynamics at the Ionic Liquid/Au(111) Interface: A Molecular‐Scale In Situ Video‐STM Study (Angew. Chem. Int. Ed. 20/2015). Issue 20 (27th April 2015) - Wen, Rui; Rahn, Björn; Magnussen, Olaf M.
<x xml:space="preserve">Abstract</x> Shrouded in mystery , the interface structure of ionic liquids is unclear despite their popularity for electrochemical applications. In their Communication on page 6062 ff., O. M. Magnussen et al. address the molecular arrangement and sub‐second dynamics of these iconic compounds on gold electrodes by high‐speed tunneling microscopy. With decreasing potential, distinct transitions in the structure and surface mobility of the innermost layer of 1‐butyl‐1‐methylpyrrolidinium cations are found.